Effect of Business Digitalization and Social Media on MSME Performance with Digital Competence as a Mediating Variable - Titin; Sutrisno; Mahmudah, Henny; Muhtarom, Abid; Syamsuri (Scientific Journal of Informatics, 2024)
Abstract. Purpose: The advancement of digital technology has fundamentally transformed the business landscape. Business digitalization and social media utilization have emerged as key drivers in SME strategies to enhance performance. This research aims to assess the effect of business digitalization and social media utilization on SME performance and to examine the role of digital competence as a mediator in this relationship. Method: This study employed a quantitative approach utilizing SEM-PLS methodology to explore the interrelationships among relevant variables. The study was conducted on 51 SMEs in Lamongan Regency, Indonesia, using an online questionnaire as the data collection tool. Result: The study findings revealed that business digitalization, social media utilization, and digital competence have a significant and positive effect on SME performance in Lamongan Regency. Moreover, digital competence is a significant mediator between business digitalization, social media utilization, and SME performance. These findings underscore that digital competence enables SMEs to optimize the benefits of business digitalization and social media, thereby enhancing operational efficiency, expanding market reach, and adapting to market changes swiftly and effectively. Novelty: In particular, the implementation of digital technology in production processes, integration of digital systems in business management, social media utilization for marketing and customer interaction, and the development of digital competence are key factors in enhancing operational efficiency, reducing costs, increasing sales and revenue, and improving customer satisfaction and loyalty among MSMEs.